2011
DOI: 10.1182/blood-2010-10-310789
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive prenatal diagnosis of hemophilia by microfluidics digital PCR analysis of maternal plasma DNA

Abstract: Hemophilia is a bleeding disorder with X-linked inheritance. Current prenatal diagnostic methods for hemophilia are invasive and pose a risk to the fetus. Cell-free fetal DNA analysis in maternal plasma provides a noninvasive mean of assessing fetal sex in such pregnancies. However, the disease status of male fetuses remains unknown if mutation-specific confirmatory analysis is not performed. Here we have developed a noninvasive test to diagnose whether the fetus has inherited a causative mutation for hemophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
160
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(166 citation statements)
references
References 32 publications
0
160
0
6
Order By: Relevance
“…Therefore, this approach is mostly useful for diagnosis of mutations that are inherited from the father and are absent in the mother's genome. To overcome this problem, an approach called the relative mutation dosage was developed [58,59]. This method includes accurate quantification of the relative dosage of the mutant and wild-type alleles in plasma.…”
Section: Cell-free Fetal Dna and Mrna In Maternal Bloodmentioning
confidence: 99%
“…Therefore, this approach is mostly useful for diagnosis of mutations that are inherited from the father and are absent in the mother's genome. To overcome this problem, an approach called the relative mutation dosage was developed [58,59]. This method includes accurate quantification of the relative dosage of the mutant and wild-type alleles in plasma.…”
Section: Cell-free Fetal Dna and Mrna In Maternal Bloodmentioning
confidence: 99%
“…6 We have previously reported that it is feasible to perform NIPT for fetal genotype assessment by maternal plasma DNA analysis of F8 and F9 sequence variants by microfluidics digital PCR (dPCR). 7 The European Hematology Association Roadmap for European Hematology Research has identified development in NIPT for hemophilia as a research priority, in particular for severe and common sequence variants such as F8 int22h-related inversions. 8 The well-established hemophilia A and hemophilia B databases gather detailed descriptions of more than 2000 sequence variants occurring in the F8 gene and approximately 1000 sequence variants in the F9 gene, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This can potentially be resolved through a haplotypebased analysis examining mutation-linked polymorphic sites. [16][17][18] The protocol described by Tsui et al 7 for NIPT of hemophilia assesses the allelic imbalance from the proportion of the mutant (M) and normal/wild-type (N) allele in maternal plasma of pregnant hemophilia carriers. As for any NIPT-based protocol using a molecule counting strategy, the fetal DNA fraction governs the degree of such allelic imbalance, and thus requires precise molecular tools for its measurement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lo auf dem Gebiet der nicht-invasiven pränataler Testung (NIPT) gegeben, der schon 1999 erste Arbeiten zur pränatalen Untersuchung zirkulierender fetaler DNA im mütterlichen Plasma vorstellte [7][8][9]. In 2010 konnte er zeigen, dass sich das gesamte fetale Genom aus seiner im mütterlichen Plasma zirkulierenden DNA sequenzieren ließ [10] und in 2011 stellte seine Gruppe eine nicht-invasive pränatale Diagnostik der fetalen Hämophilie bei heterozygoten Schwangeren vor [11].…”
Section: Introductionunclassified